UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI: DAMPAK PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP AGRESIVITAS PAJAK - Rizqi, Reza Muhammad; Akbar, Arya Zulfikar; Fahlia, Fahlia (Ultimaccounting Jurnal Ilmu Akuntansi, 2025)
Abstract - This study analyzes the impact of profitability and sales growth on tax aggressiveness, using company size as a moderating variable. The primary issue addressed is the tax aggressiveness practiced by consumer goods companies listed on the Indonesia Stock Exchange (IDX). The drive to maximize profitability in a competitive environment and the perception of high tax rates are the main reasons these companies exploit legal loopholes in complex tax regulations to minimize their tax burden. The study underscores the significant role of firm size, especially for tax authorities assessing aggressive tax strategies. Findings indicate that regulators should closely monitor larger firms, which are more likely to engage in tax avoidance despite strong profitability and sales growth. This quantitative research employs an explanatory method to examine causal relationships between variables. The sample includes consumer goods companies listed on the IDX from 2021 to 2023. Using purposive sampling, 174 data points were collected from 58 companies over three years. Multiple regression analysis was conducted using EViews 12. Results show that profitability and sales growth positively and significantly influence tax aggressiveness. Furthermore, company size enhances the positive effect of both profitability and sales growth on tax aggressiveness. All four research hypotheses are supported, offering insights into tax behavior in Indonesia’s consumer goods sector. Keywords: Tax Aggressiveness; Sales Growth; Profitability; Company Size; Tax Regulation